The Role Of Musyrifah In Providing Informative Social Support To Students In Islamic Boarding School - Ramadiana, Nasywa Nurlia; Dayati, Umi; listyaningrum, Anggia (Proceedings Series of Educational Studies, 2024)
Islamic boarding schools are educational institutions that include formal, non-formal and informal education. In Islamic boarding schools, the figure of Musyrifah is used as a caregiver for the students who has the role of guiding the students. The musyrifah who guides the students must provide attention, care, advice, support and good problem solving to the students. The approach given to students must also be appropriate, students prefer musyrifah who can be friends and provide sufficient attention. However, in reality there are musyrifah who make mistakes in their approach to students, so that the students feel uncomfortable in the presence of musyrifah. In response to this, Musyrifah needs the correct method of approach to students so that students are comfortable with Musyrifah's presence, can be open to Musyrifah, and also the support provided by Musyrifah can be channeled well. Apart from that, students need informative social support in the form of suggestions, advice, ideas, input, and providing internet access to support students while they are at the Islamic boarding school. This research uses a qualitative research method with a phenomenological approach. This research is located at the Ar-Rohmah Putri Islamic Boarding School. The research subjects chosen were based on predetermined criteria, namely musyrifah and santri. In this research, researchers used data collection techniques in the form of observation, interviews and documentation. This research also uses technical triangulation and time triangulation to obtain valid research results. The results of this research, the role of a musyrifah in providing informative social support, can have an impact on the openness of students to musyrifah and make it easier for students to be able to face Islamic boarding school life which includes school activities and dormitory activities. The purpose of this research is that the researcher wants to find out how much impact the role of a musyrifah has in providing informative social support to students in Islamic boarding schools, and also the researchers want to know what kind of role of a musyrifah the students can accept well. Keywords: The Role of Musyrifah, Santri, Informative Social Support